Sanksi Pidana Bagi Pelaku Poligami dalam Kitab Undang-Undang Hukum Pidana (KUHP) Dalam Perspektif Hukum Islam dan Sistem Hukum Nasional - Muhammad Afdhal Askar (Bertuah: Journal of Sharia and Islamic Economics, 2021)
Polygamy marriages have been going on for a long time for some people in Indonesia. The practice of polygamy is usually also motivated by several factors such as household harmony, absence of offspring, biological reasons and so on. However, with the enactment of the Criminal Code through the concordance principle which has led to legal unification hitherto, the practice of polygamy which is carried out outside the provisions of the legislation is determined to be a crime that is threatened with a criminal sanction. In its continuation, this creates a lot of controversy to Indonesian people because polygamy is basically a sharia and something that has been going on for a long time in some Indonesian people. Therefore, criminal sanctions according to Article 279 of the Criminal Code paragraph (1) and (2) to polygamy actors need to be reviewed because it is not in line with the source of material law in Indonesia, namely Pancasila and protection of human rights in practicing religion in accordance with religion and belief. . This writing is carried out through normative juridical research with qualitative research.